Recent Updates on Peptide Molecules in Drug and Vaccine Development - Sarfaraz, Mamoona; Anjum, Faiqa; Zahra, Duaa; Maqsood, Ayesha; Ashfaq, Usman A. (Current Pharmaceutical Design, 2023)
Peptides are of great importance in the areas of science because they can act as drug carriers and their therapeutic effect and their ability to generate an immune response. As culturing of viral agents for drugs and vaccine development is harmful, therefore, peptide-based drugs and vaccines have achieved great importance. Large immunoglobulins cannot pass the plasma membrane, so peptides are used to study this interaction because of their small size. Peptides with substituted amino acid sequences are also stable in blood serum, which makes them significant for drug development. Peptides with substituted amino acid sequences are stable in blood serum hence, their stability, small size, easy screening, cost-effectiveness, ease of administration and particularity (target specificity) make them effective to be used in pharmaceutical companies. Mostly branched peptides are used for the development of drugs because they are not prone to be degraded by proteolytic enzymes. In peptide-based vaccines, protein acts as the main constituent from which the main component that causes the infection is deleted by recombinant DNA technology, and these peptides act as antigens to stimulate the immune response. Self-assembled peptides have the main role in the delivery of drugs and vaccine molecules inside the living cells because they may also assemble into nano technological structures to improve their efficiency. This review focuses on the characteristics of peptides that make them effective to develop drugs and vaccines. Different peptides like synthetic peptides, antimicrobial peptides, signal peptides, carrier peptides, and their role against various viral, pathogenic, and microbial diseases and in cosmetics are described briefly.
Keywords: immune responses